LINGUO-PRAGMATIC TYPOLOGY OF METAPHORS: THE INTERSECTION OF LANGUAGE AND PRAGMATICS (Scientific journal of the Fergana State University, 2024)
This study examines the linguo-pragmatic typology of metaphors, highlighting the intersection of language and pragmatics. By exploring various metaphorical constructs across languages, this research aims to uncover the pragmatic functions and implications of metaphors in communication. The investigation employs both qualitative and quantitative methodologies, analyzing data from diverse linguistic sources. The findings reveal significant variations in metaphor usage and comprehension, influenced by cultural and contextual factors. These insights contribute to a deeper understanding of how metaphors function pragmatically, enhancing our knowledge of language use in different sociocultural settings.